The reasons behind the US military's preparations indicate a growing focus on potential conflicts with China ... - Sopory, Tejasv (Zenodo, 2024)
This paper examines the strategic military and geopolitical developments between the United States, China, and their regional allies, highlighting the intensifying focus on potential conflicts in the Asia-Pacific and Arctic regions. The militarization of Japan’s Mageshima Island, alongside the broader buildup in the South China Sea, reflects a significant shift in U.S. force posture, aimed at countering China’s influence. Additionally, the evolving roles of India and the AUKUS pact underscore the global realignment of power. The paper also explores the strategic importance of Greenland and the Arctic, where climate change is opening new geopolitical opportunities and tensions. ...